Contemplative studies in higher education - Sanders, Linda A. (New directions for teaching and learning, 2013)
The complexities of 21st-century life-personal, social, cultural, and environmental-demand thoughtful responses, responses fostered and enhanced through contemplative experience. Contemplative education includes studies of the history, psychology, and socialcultural context of such experience, as well as the development of experiential knowledge through one or more personal practices. Contemplative education has recently emerged in the academy. Although there has been significant published discussion of postsecondary courses and programs that incorporate contemplative views and practi
Keywords: Contemplation : Study and teaching (Higher); Meditation : Study and teaching (Higher); Universities and colleges : Curricula; Education, Higher : Curricula